Mutant p53-microRNA-200c-ZEB2-Axis-Induced CPT1C Elevation Contributes to Metabolic Reprogramming and Tumor Progression in Basal-Like Breast Cancers - Wang, Chen-Yun; Wang, Cing-Hong; Mai, Ru-Tsun; Chen, Ting-Wen; Li, Chia-Wei; Chao, Chi-Hong (Frontiers in Oncology, 2022)
TP53 is mutated in more than 80% of basal-like breast cancers (BLBCs). BLBCs with TP53 mutation are usually high-grade and have worse responses to chemotherapy, leading to poor clinical outcomes. Wild-type p53 (WTp53) is well-accepted to promote fatty acid oxidation (FAO); however, in this study, we demonstrate that mutant p53 (Mutp53) enhances FAO activity through constitutively upregulating CPT1C via dysregulating the miR-200c-ZEB2 axis. Sustained CPT1C expression contributes to the metabolic preference of FAO, epithelial-mesenchymal transition (EMT) phenotypes, migration, invasion, and cancer stemness in BLBC, which is mediated by modulating the redox status. Furthermore, interference of CPT1C expression impairs tumor growth and pulmonary colonization of BLBC cells in vivo, and even postpones the occurrence of spontaneous metastasis, resulting in a prolonged disease-specific survival (DSS). Consistently, clinical validation reveals that high CPT1C is observed in breast cancer patients with metastasis and is correlated with poor overall, disease-free, progression-free, and disease-specific survival in BLBC patients. Together, unlike WTp53 which transiently transactivates CPT1C, Mutp53 provides long-term benefits through sustaining CPT1C expression by disturbing the miR-200c-ZEB2 axis, which potentiates FAO and facilitates tumor progression in BLBC, suggesting that targeting Mutp53-CPT1C-driven metabolic reprogramming is promising to serve as novel therapeutic strategies for BLBC in the future.